Migrants’ Mental Maps: Unpacking Inhabitants’ Practical Knowledges in Lisbon - Buhr, Franz (2021)
A common consequence of sticking to a research topic for a fair amount of time is that it starts colonising your everyday life to a point where you may find yourself asking questions to every new acquaintance as if they were participants in your project. Your friends may become tired of your constant interrogations, but unknown people might simply take you as someone with a peculiar sense of curiosity. I believe this is what recently happened to me when coming back from a conference and decided to call an Uber driver at Lisbon airport. This chapter explores some of the functionalities mental maps offer to migration research. Mental maps (or cognitive maps) have long helped understanding how individuals use and perceive local space. Yet, as a visual method, mental maps may be produced and analysed in distinct ways. This chapter navigates through existing research employing mental maps and argues for an interactive approach to mental map analysis, in which the researcher-participant engagement becomes as fundamental as the actual visualisation produced. Based on fieldwork with migrants in Lisbon, Portugal, the chapter illustrates the methodological potential of mental maps for yielding information about the ways migrants actively mobilise urban resources.